Big Hole: Excavating intimate histories of a nuclear homefront. Issue 4 (2nd October 2021) - Kastleman, Rebecca
ABSTRACT: Growing up in the woods of Chatham County, North Carolina, among families who had decided to go back to the land, I imagined that nuclear conflict was worlds away—until I discovered that a top-secret federal communications facility had been hiding in my family's backyard. This covert facility, known as the 'Big Hole' and operated by AT&T, is one of a small network of 'continuity of government' sites that were designed to shelter top federal officials in the event of a nuclear attack. After a period of disuse, the Big Hole site has recently come back online. This essay traces my attempt to understand its purpose and place in the terrain of my childhood home. As I show, the persistent growth of U.S. domestic defense infrastructure is at least partially reversible at the level of local government, for citizens possess the power to check the expansion of these secret installations. Even so, the infrastructure of defense place limits on individuals' ability to understand and even to access their own lived environments. These military architectures have become pervasive and enduring features of our living landscape.